Phenotypic Modification of Human Airway Epithelial Cells in Air–Liquid Interface Culture Induced by Exposure to the Tobacco-Specific Nitrosamine 4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK). (April 2015) - Carson, Johnny L.; Brighton, Luisa E.; Jaspers, Ilona
Abstract The nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) is a potent tobacco-specific carcinogen. We used an air–liquid interface epithelial cell culture system to model changes associated with NNK exposure relative to pathologies documented in human tobacco-related illnesses. Although in vitro systems exhibit certain limitations, they often offer accentuation of subtle pathologies. While the distribution of cell types in control cultures typically favors the ciliated cell phenotype, NNK-exposed cultures transitioned to non-ciliated cell phenotypes as well as reflecting features consistent with squamous metaplasia. We conclude that NNK impacts normal growth and differentiation of human airway epithelium in a short interval of time in vitro.